Titans of the twentieth century: how they made history and the history they made - Mandelbaum, Michael (New York, USA : Oxford University Press, 2024)
"The Titans of the Twentieth Century addresses an age-old question: what is the impact of individuals on history? The first half of the twentieth century offered political leaders enormous scope for changing the world. This book consists of essays about eight who, for better and for worse, did just that. Woodrow Wilson had a vision for a cooperative world order that failed after the First World War but gained in influence after the Second. Vladimir Ilich Lenin founded the totalitarian communist political system that controlled a large part of the planet for much of the twentieth century. Adolf Hitler started history's worst war and presided over history's worst atrocity, the Holocaust. Winston Churchill provided inspiring leadership to Great Britain, which made it possible to defeat Nazi Germany in World War II"--
Thomas Woodrow Wilson -- Vladimir Ilich Lenin (Ulyanov) -- Adolf Hitler -- Winston Leonard Spencer Churchill -- Franklin Delano Roosevelt -- Mohandas Karamchand Gandhi -- David Ben-Gurion (Gruen) -- Mao Zedong.
Includes bibliographical references and index.
Keywords: Heads of state -- Biography; Biography -- 20th century; History, Modern -- 20th century -- Historiography; Statesmen -- Biography; World politics -- 20th century